Echocardiography findings after intravenous injection of Achillea millefolium (Yarrow) extract in the dog - Yadegari, M.; Khamesipour, F.; Talebiyan, R.; Katsande, S. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Achillea millefolium (yarrow) has been used for centuries as medicinal plant to treat different disorders in human and in traditional medicine to treat hypertension, diarrhea and shigellosis, heart failure, heart block and chest pain in thrombotic condition. There are no studies done on echocardiography in situ findings from intravenous injection Achillea millefolium extract in the dog. Therefore, a study was designed to evaluate echocardiography dynamics from intravenous injection of A. millefolium ethanolic leave extract in the male dog. This research was performed on 6 healthy male mongrel (breed) dogs in weight range of 15-30kg and age mean of 3 years. Echocardiography was performed before drug injection and then in times of 0, 60, 120 minutes after injection. Then left ventricular diameters in systole (LVDs), left ventricular diameters in diastole (LVDd), left ventricular septal thickness at end-systole (LVSs), left ventricular free wall systole (LVFWs), left ventricular free wall diastole (LVFWd), stroke volume (SV) and fractional shortening (FS) indices were measured. Mean and standard deviation was measured for each of indices in each period and were analyzed using paired t-test using SPSS as statistical software. SV, FS and EF indices before and 120 minutes after injection in 6 tested dogs showed significant difference statistically. This can be attributed to effect of alkaloids and unknown compounds available in A. millefolium on cardiovascular system which initially decreases blood pressure. Consequently, heart rate is increased to compensate blood pressure decreasing by activation of baroreflex and then stroke volume increases because of decreasing in afterload and increasing in preload. Antispasmoic property of compound presented in this plant decreases myocardium contraction power and in result heart fractional shortening is decreased.